Understanding the information needs of women with rheumatoid arthritis concerning pregnancy, post-natal care and early parenting: A mixed-methods study - Ackerman, I.; Jordan, J.; Van Doornum, S.; Ricardo, M.; Briggs, Andrew (BioMed Central Ltd., 2015)
© 2015 Ackerman et al. Background: Although women with rheumatoid arthritis (RA) face a number of challenges in negotiating the journey to parenthood, no studies have explored the information needs of women with RA in relation to their childbearing years. This study aimed to determine the need for (and preferred mode/s of delivery of) information regarding pregnancy, post-natal care and early parenting among women with RA. Methods: Interviews and focus groups were conducted with 27 women with RA who were pregnant in the last 5 years, currently pregnant or planning pregnancy. Verbatim transcripts were analysed using both inductive and deductive approaches. Two validated instruments were used to quantify information needs and preferences: the Educational Needs Assessment Tool (ENAT, range 0-156, higher scores indicate higher educational needs) and the Autonomy Preference Index (API, range 0-100, higher scores indicate stronger preferences). Results: Lack of information about medication safety, access to physical/emotional support services and practical strategies for coping with daily challenges related to parenting were the most prominent of the six key themes identified. Rheumatologists were the primary source for information regarding treatment decisions while arthritis consumer organisations were perceived as critical 'resource hubs'. There was strong preference for information delivered electronically, especially among rural participants. Quantitative outcomes supported the qualitative findings; on average, participants reported high educational needs (mean ENAT score 97.2, SD 30.8) and API scores indicated that desire for information (mean 89.8, SD 5.6) was greater than the need for involvement in treatment decision-making (mean 68.4, SD 8.2). Conclusions: Many women with RA struggle to find adequate information on pregnancy planning, pregnancy and early parenting in relation to their chronic condition, and there is a clear need to develop accessible information that is consumer-focused and evidence-based. Although most participants trusted their rheumatologist as their primary information source, there was consistent demand for more information, particularly regarding the safety of RA medications during pregnancy and breastfeeding, and the importance of learning from other women's personal experiences was strongly emphasised.